Correlação entre parâmetros da espirometria e complicações após cirurgia bariátrica em obesos mórbidos - Zanatto, Daniela Ogawa (2025)
Obesity is a chronic disease that affects thousands of patients worldwide. Bariatric surgery has emerged as a safe and effective alternative for treating obesity and controlling comorbidities in patients who have not been able to sustain weight loss through non-surgical means. The complication rate after bariatric surgery is approximately 0.2 to 10%. The relationship between preoperative spirometry parameters and complications after bariatric surgery remains controversial. Objective: To describe spirometric changes in morbidly obese individuals (BMI>40) before bariatric surgery and correlate them with the development of postoperative complications. Method: Cross-sectional study that evaluated 116 patients with morbid obesity (BMI>40) who underwent bariatric surgery between May 2012 and December 2017. After descriptive analysis, we used the Univariate Logistic Regression model to verify the relationship between spirometric parameters, forced expiratory volume in one second (FEV1), forced vital capacity (FVC) and FEV1/FVC in the preoperative period and the development of complications in the postoperative period. Results: Gastric bypass bariatric surgery (BPG) was performed in 99.1% of patients, 75% were female, the mean age of patients was 36.6 years and the mean initial BMI was 59.71 kg/m². Most patients (69.0%) did not present any complications, while the remaining patients presented grade I (4.3%), grade II (25.0%) and grade III-B (1.7%) complications. In the group of patients without complications, the median FVC (% predicted) was 88.21%, the median FEV1 (% predicted) was 86.43% and the median FEV1/FVC (% predicted) ratio was 98.94%. In the group of patients with complications, the median FVC (% predicted) was 78.56%, the median FEV1 (% predicted) was 75.53% and the median FEV1/FVC (% predicted) ratio was 96.95%. Conclusion: In this study, it was found that the decrease in FEV1 levels <80% and FVC <80% in morbidly obese patients before bariatric surgery increased the risk of postoperative complications.